2018
DOI: 10.1007/s40121-018-0189-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Strategies for Providing Fecal Microbiota Transplantation to Treat Patients with Recurrent Clostridium difficile Infection in Two English Hospitals: A Review

Abstract: Fecal microbiota transplant (FMT) has emerged as a highly efficacious treatment for difficult cases of refractory and/or recurrent Clostridium difficile infection (CDI). There have been many well-conducted randomized controlled trials and thousands of patients reported in case series that describe success rates of approximately 90% following one or more FMT. Although the exact mechanisms of FMT have yet to be fully elucidated, replacement or restoration of a ‘normal’ microbiota (or at least a microbiota resemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 97 publications
0
50
0
1
Order By: Relevance
“…It is not known whether a change of the microbiota following FMT has any long-term consequences. Despite a few worldwide existing stool banks, there is no standard method for producing material for FMT, and there are a multitude of factors that can vary between institutions offering this therapy [23]. To date, safety concerns and acceptability are the main constraints of therapeutic uses of FMT [24].…”
mentioning
confidence: 99%
“…It is not known whether a change of the microbiota following FMT has any long-term consequences. Despite a few worldwide existing stool banks, there is no standard method for producing material for FMT, and there are a multitude of factors that can vary between institutions offering this therapy [23]. To date, safety concerns and acceptability are the main constraints of therapeutic uses of FMT [24].…”
mentioning
confidence: 99%
“…[4] FMT involves the introduction of microbiota from a healthy donor to a patient by colonoscopy, enema or nasogastric tube. [5] Currently, CDI is the main indication for FMT, but as a novel treatment strategy, it has also been investigated in conditions ranging from inflammatory bowel disease to metabolic diseases, obesity, malnutrition and autism spectrum disorders. [6] To this end, the SA Gastroenterology Society (SAGES) published FMT guidelines in 2015.…”
Section: Editorialmentioning
confidence: 99%
“…In an attempt to increase intestinal microbial diversity and re-establish a stable microbiome, fecal microbiota transplantation (FMT) has been applied to the treatment of recurrent CDI [6] and other gastrointestinal disorders [7]. The reported success rate of FMT based on thousands of patients with recurrent CDI is 90% following one or more FMT [8,9]. Although restoration of a microbiota appears to have a positive effect against gut dysbiosis that is thought to exist in these patients, the exact mechanisms of FMT have yet to be fully elucidated [8].…”
Section: Introductionmentioning
confidence: 99%
“…The reported success rate of FMT based on thousands of patients with recurrent CDI is 90% following one or more FMT [8,9]. Although restoration of a microbiota appears to have a positive effect against gut dysbiosis that is thought to exist in these patients, the exact mechanisms of FMT have yet to be fully elucidated [8]. In addition to gastrointestinal disorders, recent studies have shown promising applicaiton of FMT to treat other types of diseases, including Parkinson's disease [10] and autism [11].…”
Section: Introductionmentioning
confidence: 99%